IMPLIMENTASI PENGGUNAAN ANGGARAN DESA PRESPEKTIF UU NOMOR 6 TAHUN 2014 TENTANG DESA - Saleh, M.; Khair, Abdul; Sarkawi, Sarkawi; Kafrawi, Kafrawi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This research is a normative legal research, using the conceptual approach and legislation. The purpose of this study was to see the implementation of the use of the village budget as regulated in the village law. Research result; the use of village funds as stated in the 2014 Village Law, that the use of old village funds for village development is in accordance with local village conditions. The allocation of the use of village funds is based on statutory regulations and village needs that have been considered in the APBDes within 1 (one) fiscal year.